Odpowiedź:
1.
4a²+4a+1=(2a+1)² ODP . A
2
(5x-2)²-4=25x²-20x+4-4=25x²-20x ODP C
3.
a)(3x-2)(4x+3)=12x(x-1)
12x²+9x-8x-6=12x²-12x
12x²-12x²+x+12x=6
13x=-6:13
x=6/13
b)(x-2)²-6=(x-3)(x+3)
x²-4x+4-6=x²-9
x²-x²-4x=-9+2
-4x=-7/(-4)
x=7/4
4.
(x-2)²-4≥x(x-4)
x²-4x+4-4≥x²-4x
0≥0
x∈R
5.
a)(1/2x+5)²=1/4x²+5x+25
b)(4-√2x)²=16-8√2x+2x²
c)(0,6x+√5)(0,6x-√5)=0,36x²-5
6
a)(2x³-x)(x³+2x-3)=
2[tex]x^{6}[/tex]+4[tex]x^{4}[/tex]-6x³-[tex]x^{4}[/tex]-2x³+3x=2[tex]x^{6}[/tex]+3[tex]x^{4}[/tex]-6x³-2x²+3x
b)(3-x)-(2x-1)(1-2x)=
3-x-(2x-4x²-1+2x)=3-x-2x+4x²+1-2x=4x²-5x+4
7.
[tex]\frac{\sqrt{3}}{2+\sqrt{5}}=\frac{\sqrt{3}*(2-\sqrt{5}}{2+\sqrt{5})(2-\sqrt{5}}=\frac{2\sqrt{3}-\sqrt{15}}{4-5}=-2\sqrt{3}+\sqrt{15}[/tex]
8.
a)I5 1/2I+I-5 1/2I=5 1/2+5 1/2=11
b)I4-√7I=4-√7
Szczegółowe wyjaśnienie: